2006
DOI: 10.1111/j.1475-6773.2006.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

State‐Mandated Benefit Review Laws

Abstract: Objective. To determine which states have laws that require the review of mandated health insurance benefits and describe the various approaches states take in reviewing mandated benefits, as stated in the mandated benefit review (MBR) laws. Data Sources. We queried online databases of the individual state statutes and reviewed the state statutes and state legislative agendas for all 50 states and Washington, DC to identify those states with active MBR laws as of September 2004. Study Design. We reviewed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…3.3.1 Mandate review boards. According to Bellows et al (2006), 26 states have established mandate review boards. These boards issue reports on proposed mandates, attempting to predict their effects.…”
Section: Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.3.1 Mandate review boards. According to Bellows et al (2006), 26 states have established mandate review boards. These boards issue reports on proposed mandates, attempting to predict their effects.…”
Section: Institutionsmentioning
confidence: 99%
“…Data on mandate review boards come from Bellows et al (2006). They identify 26 states with review boards as of 2006 and provide the year that each board began.…”
Section: Data and Empirical Strategy 41 Data Sourcesmentioning
confidence: 99%
“…In general, state benefit mandates require health insurers and/or health plans to provide coverage for a specific group of people (e.g., dependants), coverage for a specific disease or condition (e.g., Lyme disease or infertility), reimbursement for services provided by specific types of providers (e.g., podiatrists or nurse midwives), reimbursement for certain types of medical devices or pharmaceuticals (e.g., hearing aids or Chantix), or provide reimbursement for a minimum quantity of benefits (e.g., coverage for minimum hospital stay after mastectomy). 81 Since the 1970s, these mandates, the overwhelming majority of which do not cover preventive services, have grown in number, and more are enacted every year. 82 Many reasons have been cited to explain the proliferation of state benefit mandates.…”
Section: Symposiummentioning
confidence: 99%
“…A study of states with mandate review laws as of September 2004 found that twenty‐five of twenty‐six states stipulated that reviewers use specific criteria to evaluate the bills. Furthermore, twelve of these states (48 percent) required reviewers to examine the medical effectiveness of the technologies or interventions that the proposed mandates would require health plans and health insurers to cover (Bellows, Halpin, and McMenamin 2006).…”
Section: Mandated Benefit Review Lawsmentioning
confidence: 99%